Recent Patents on Light-Based Anti-Infective Approaches - Ahmed, Imran; Fang, Yanyan; Lu, Min; Yan, Quan; El-Hussein, Ahmed; Hamblin, Michael R.; Dai, Tianhong (Recent Patents on Anti-Infective Drug Discovery, 2018)
Background: Antibiotic resistance is one of the most serious health threats to modern medicine. The lack of potent antibiotics puts us at a disadvantage in the fight against infectious diseases, especially those caused by antibiotic-resistant microbial strains. To this end, an urgent need to search for alternative antimicrobial approaches has arisen. In the last decade, light-based anti-infective therapy has made significant strides in this fight to combat antibiotic resistance among various microbial strains. This method includes utilizing antimicrobial blue light, antimicrobial photodynamic therapy, and germicidal ultraviolet irradiation, among others. Light-based therapy is advantageous over traditional antibiotics in that it eradicates microbial cells rapidly and the likelihood of light-resistance development by microbes is low. Methods: This review highlights the patents on light-based therapy that were filed approximately within the last decade and are dedicated to eradicating pathogenic microorganisms. The primary database that was used for the search was Google Patents. The searches were performed using the keywords including blue light, antimicrobial photodynamic therapy, ultraviolet irradiation, antibiotic resistance, disinfection, bacterium, fungus, and virus. Results: Forty-five patents were obtained in our search: 9 patents for the antimicrobial blue light approach, 21 for antimicrobial photodynamic therapy, 11 for UV irradiation, and lastly 4 for other light-based anti-infective approaches. The treatments and devices discussed in this review are interestingly enough able to be used in various different functions and settings, such as dental applications, certain eye diseases, skin and hard surface cleansing, decontamination of internal organs (e.g., the stomach), decontamination of apparel and equipment, eradication of pathogenic microorganisms from buildings and rooms, etc. Most of the devices and inventions introduce methods of destroying pathogenic bacteria and fungi without harming human cells and tissues. Conclusions: Light-based antimicrobial approaches hold great promise for the future in regards to treating antibiotic-resistant infections and related diseases.
Keywords: disinfection